Sociocultural overview and predisposing factors of body art in a health promotion perspective: survey on a sample of Italian young adults - Scatigna, M.; Masotta, V.; Cesarini, V.; Renzetti, P.; Petrucci, C.; Lancia, L.; Leuter, C. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The body art (tattoos, body piercing and other aesthetic practices) is increasing at global level and involves different aspects of public health, from epidemiological feature to cultural and psychosocial determinants and regulatory issues. The study is aimed at estimating the prevalence of tattooed and pierced in youth, focusing on emerging profiles.Study design. A cross-sectional study has been conducted on 575 students at the first year of degree courses of an Italian University.Methods. Students were asked to fill an online questionnaire. Logistic regression models were evaluated in order to identify predictive factors and determinants of practice (tattoos, piercing, body art).Results. The 41.9% of participants underwent at least one body art intervention, with a higher prevalence in females. Multivariate logistic regression suggested an association of body art practice with type of school and university course, as well as lifestyle characteristics (smoking, alcohol abuse). In addition, the intention to undergo to body art intervention in the future appeared significantly higher in women and more frequent in apparently ‘protected’ categories such as medical students and non-problematic alcohol users.Conclusions. The study confirmed the importance of the surveillance and social and behavioural research on body art practice and suggested different health promotion perspectives, such as early intervention towards adolescents and late intervention towards young adults belonging to lesser risky population groups.